Thoughts and Philosophy of Ibn Bajjah - Hasnah Nurhalimah; Mutiara Finnegan Devina; Zaki Rizanata (Penerbit Hellow Pustaka, 2025)
Around the 8 century. Islam is landed in Andalusia (Spain). It has opened new horizons in history of Islam. In lapse of seven half a century, Muslim in Andalusia had achieved significant progress, in the fields of knowledge and culture. Various disciplines growing fast at that time. This was marked with the number of the scientists who bright in their respective fields so far, the result of their thoughts is cited by academics, both in the West and in the Middle East. One of the glorious things who was felt by Andalusian is philosophy. Abu Bakr Muhammad ibn al-sayigh also known as Ibn Bajjah is the personage of philosophy in Andalusia. His famous opus is contained in his magnum-opum entitled Tadbir al-Mutawahhid. “Avempace” is the name who given by European for Ibn Bajjah. According to some literature, Ibn Ibn Bajjah is not only an ansich philosopher, but also a scientist who take over several disciplines of knowledge, such as medicine, astronomy, music, and math. The others popular works from Ibn Ibn Bajjah, namely Tadbirul Mutawahhid and Risalatul-Ittishal. Tadbirul-Mutawahhid is a book about moral and political inspired from Al- Madinatul-Fadhilah from Al-Farabi. Risalatul-Ittishal Ibn Ibn Bajjah divided man in three classes, namely: the laity (al-jumhur), an-nudzdzar (the khawas or intellectuals) and the people who are happy.